GROUPER FINGERLING/SEEDS AND NURSING GROUND IN THI NAI, CU MONG LAGOON AND QUY NHON BAY - Quang, Vo Van; Thao, Le Thi Thu; Vu, Nguyen Phi Uy; Hoa, Tran Thi Hong; Thinh, Tran Cong (Vietnam Journal of Marine Science and Technology, 2016)
The wild grouper fingerling have provided the important seed source for the development of commercial fish farming. Among the wild grouper fingerling collected in the Thi Nai lagoon, Quy Nhon bay (Binh Dinh) and Cu Mong lagoon (Phu Yen), 7 species of grouper have been identified as Banded grouper (Epinephelus amblycephalus), Yellow grouper (E. awoara), Longtooth grouper (E. bruneus), Malabar grouper (E. malabaricus), Sixbar grouper (E. sexfasciatus), Orange-spotted grouper (E. coioides) and grouper (Epinephelus sp.); in which three species of Longtooth grouper, Malabar grouper and Orange-spotted grouper were endangered in Red List Categories & Criteria of IUCN as VU and NT. The Malabar grouper seed makes up a high proportion of over 30%. The total length of the juveniles is different between species, ranging from an average of 25.0 mm to 116.82 mm; Orange-spotted grouper is 112.48 mm in total length; four grouper species Banded grouper, Yellow grouper, Longtooth grouper and Malabar grouper are longer than 30 mm in total length with 31.96, 32.23, 33.78 and 33.86 mm respectively. The Sixbar grouper and grouper (Epinephelus sp.) are smaller than 30 mm. The catching of grouper fingerling is distributed in wide area, along the bank, mangroves in the lagoon, along the western shore of the Quy Nhon bay, from Ghenh Rang to the southern part of the coast and along the Cu Mong lagoon (from south to southwest). The production of grouper seed fluctuates irregularly, 3 - 4 million seeds per year for highest yields, alternating with very low yields. The protection of nursing grounds is necessary with the solution of selective catching and limiting artisanal fishing.